Synthesis of 5'-thiamine-capped RNA - Möhler, Marvin; Höfer, Katharina; Jäschke, Andres (Molecules, 2020)
RNA 5'-modifications are known to extend the functional spectrum of ribonucleotides. In recent years, numerous non-canonical 5'-modifications, including adenosine-containing cofactors from the group of B vitamins, have been confirmed in all kingdoms of life. The structural component of thiamine adenosine triphosphate (thiamine-ATP), a vitamin B1 derivative found to accumulate in Escherichia coli and other organisms in response to metabolic stress conditions, suggests an analogous function as a 5'-modification of RNA. Here, we report the synthesis of thiamine adenosine dinucleotides and the preparation of pure 5'-thiamine-capped RNAs based on phosphorimidazolide chemistry. Furthermore, we present the incorporation of thiamine-ATP and thiamine adenosine diphosphate (thiamine-ADP) as 5'-caps of RNA by T7 RNA polymerase. Transcripts containing the thiamine modification were modified specifically with biotin via a combination of thiazole ring opening, nucleophilic substitution and copper-catalyzed azide-alkyne cycloaddition. The highlighted methods provide easy access to 5'-thiamine RNA, which may be applied in the development of thiamine-specific RNA capture protocols as well as the discovery and confirmation of 5'-thiamine-capped RNAs in various organisms.